Hydrologic impact of aspen harvesting within the subhumid Boreal Plains of Alberta. Issue 26 (16th November 2018) - Thompson, Craig; Devito, Kevin J.; Mendoza, Carl A.
Abstract: This study examined the hydrological impact of harvesting aspen ( Populus tremuloides ) within the subhumid Boreal Plains of Alberta, Canada, following clear‐cutting of two stands in successive winters within a small catchment situated in glacial moraine. Impacts were evaluated using a combination of observational data collected from within the harvested catchment and an adjacent reference catchment and numerical simulations conducted with HydroGeoSphere. Sensitivity simulations evaluated the influence of post‐harvest evapotranspiration rates and variability in atmospheric conditions on the range of hydrologic response. Study results indicate that aspen harvesting had limited impact on groundwater levels and streamflows within these hydrologic systems because of the subhumid climate with low frequency of large storms, large soil‐moisture storage capacity of heterogeneous glacial materials, and high evapotranspiration rates of regenerating aspen. Despite an estimated increase in hillslope groundwater levels of up to 3 m, pond and peatland water levels increased by less than 0.3 m and were accompanied by increased streamflows of less than 10 mm. However, predicted increases in groundwater levels and streamflows were sensitive to regenerating aspen evapotranspiration rates, which can be enhanced by appropriate harvesting techniques but may be reduced by climate change. These results are consistent with previous results from within the Boreal Plains but differ from aspen harvesting studies conducted in other settings where appreciable increases in streamflows have been reported. This disparity highlights the need to consider the integrated response of the hydrologic system when evaluating impacts from disturbance and making comparisons between settings.